Four new species of the genus Racinaea (Bromeliaceae) from Ecuador - Manzanares, José M.; Gouda, Eric J. (Phytotaxa, 2013)
Four new species belonging to the genus Racinaea (formerly Tillandsia subgenus Pseudo-Catopsis, Bromeliaceae) from Ecuador are described and illustrated here. The new species R. condorensis from the province of Zamora-Chinchipe in the southern region of Ecuador is similar to R. contorta. Racinaea guacamayosensis from the Cordillera de los Guacamayos, an area close to Tena in the province of Napo, has close affinity with R. diffusa and R. penlandii. Racinaea terrestris from the province of Morona-Santiago, southern Ecuador, is also similar to R. diffusa. The new species R. tillii from the cloudy, cool mountain forest on the Amazonian side of the Andes in Napo province, is very alike R. penlandii. Distinguishing characters between these species are provided.